Hypertrophic cardiomyopathy-linked Tnnc1 variants are associated with distinct myopathic changes in slow skeletal muscle of mice - Sonu Patel; Gabriel Leite da Silva Santos; Jaelynn Florence; Aida Rahimi Kahmini; Yun Shi; Michelle Rodriguez Garcia; Bradley S. Gordon; P. Bryant Chase; Christopher Solís; Orlando Laitano; J. Renato Pinto; Michelle S. Parvatiyar (Journal of Muscle Research and Cell Motility, 2026)

Context matters: emotional responses to urban greening interventions depend on city setting - Freya M. Thomas; Luke Greenacre; Georgia E. Garrard; Richard A. Fuller; Adrian G. Dyer; Ascelin Gordon; Christopher D. Ives; Lee Harrison; Rodney Van der Ree; Sacha Jellinek; Jacinta E. Humphrey; Sarah A. Bekessy (Urban Ecosystems, 2026)
Urban green spaces deliver a remarkable range of human health and well-being benefits, and there is substantial, global effort into incorporating urban greening into the design of cities. However, intense competition for space in cities means small interstitial gaps in the urban fabric are being used for many contemporary green spaces, such as planter boxes or raised garden beds. These small urban greening interventions have become increasingly popular in recent years, especially following the COVID-19 pandemic when access to nature in cities became a key public concern. It is not yet known whether planter boxes in urbanised settings can provide well-being benefits as traditional parks and reserves have been found to. Here we show, using manipulated images, that as much as a 60% difference in a participant’s ( n = 1200) emotional response to a planter box green space is due to changes in city context. This indicates that small green spaces in cities may provide quite different well-being benefits depending on their specific urban setting. As planting context is more important than the focal details of small green space interventions for creating emotional responses in urban residents, city planning could strategically consider not just whether , but where to integrate nature into urban areas to maximise well-being outcomes for residents.

E122Q rhodopsin: pigment microspectrophotometry, photoreceptor light responses, and bleaching adaptation - Christopher J. Meredith; Annabelle N. Tran; Alapakkam P. Sampath; Gordon L. Fain; Rikard Frederiksen (Journal of Comparative Physiology A, 2026)
When the rhodopsin visual pigment of vertebrate rods absorbs light, photoisomerization of its 11- cis retinal chromophore to all-trans retinal triggers a conformational change, ultimately leading to the formation of metarhodopsin II (meta II), the active signalling state. Meta II initiates the phototransduction cascade, culminating in membrane hyperpolarization. To investigate how meta II lifetime shapes the rod photoresponse, we studied a knock-in mouse expressing E122Q rhodopsin, a mutant pigment with a shortened meta II lifetime. Microspectrophotometry confirmed that E122Q rhodopsin is blue-shifted in its absorbance spectrum and exhibits significantly faster meta II decay than wild-type (WT). Patch-clamp recordings revealed that this shortened lifetime had little effect on response kinetics or on the dominant time constant of recovery after bright flashes. However, following pigment bleaching, rods expressing E122Q showed markedly greater desensitization than WT, indicating that free E122Q opsin activates the phototransduction cascade more efficiently in darkness. To our knowledge, this is the first report of a rhodopsin mutation that alters free opsin-driven activation of phototransduction. Given that many disease-causing mutations affect dark adaptation, such opsin-based mechanisms may be more common than previously appreciated.

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Rheological assessment of printed overhang designs for starch, protein, and combined food inks - Md Ibrahim Khalil; Yashwanth Kumar Kondabathula; Ranadip Pal; Gordon F. Christopher; Farnaz Maleky; Paul F. Egan (Food Hydrocolloids, 2026)

Decoupled responses of mycorrhizal fungal communities and function to recurrent wildfire - Solomon Maerowitz-McMahan; Christopher E. Gordon; Rachael H. Nolan; Pushpinder Matta; Amaia Montalban de la Mata; Jeff R. Powell (Soil Biology and Biochemistry, 2026)

Incorporating fire severity mapping into fuel accumulation curves - Christopher E. Gordon; Luke Collins; Meaghan Jenkins; Brett P. Murphy; Trung H. Nguyen; Owen F. Price; Liubov Volkova; Christopher J. Weston; Rachael H. Nolan (Science of The Total Environment, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A Preliminary Investigation of Research Collaboration Through Scientific Paper Co-authorship in the Gulf of Mexico - Juliet Vallejo; Evelyn Roozee; Dongkyu Kim; Andrew M. Song; Christopher A. Gabler; Jasper de Vries; Antonia Sohns; Gordon M. Hickey; Owen Temby (Estuaries and Coasts, 2026)
It is well known that publications with collaborators from external institutions increase citations. This effect scales with spatial distance. There are also many barriers to long-distance collaborations, including linguistic differences, funding constraints, and the incremental costs of remote collaboration. This paper uses the Gulf of Mexico as a case study to examine long-distance research collaboration because it consists of three countries with diverse development levels and two prominent diplomatic languages, within a singular regional ecosystem of tremendous natural and economic value. This paper uses bibliometric network analysis to examine scientific research article co-authorship in the Gulf of Mexico from 2000 to 2018. The results reveal that, although inter-organizational co-authorship has increased, significant fragmentation exists between the U.S.A, Mexico, and Cuba. Large differences in technological and organizational proximity as well as research capacity between US and Mexican states in the Gulf of Mexico may make collaboration more difficult compared to other transboundary settings, such as the US-Canadian border. Centrally located organizations in the network, such as NOAA, have played a prominent role in cross-institutional research, suggesting a capacity to bridge political entities in the Gulf of Mexico.

Age-related change in skeletal muscle strength, size, and adiposity over 18 years in Caribbean men - Lauren S. Roe; Ryan K. Cvejkus; Victor W. Wheeler; Christopher L. Gordon; Tanya S. Kenkre; Joseph M. Zmuda; Iva Miljkovic (GeroScience, 2025)
Declines in muscle strength outpace declines in muscle mass with age, so factors like muscle adiposity (i.e., myosteatosis) may contribute to strength loss. We describe intermuscular adipose tissue (IMAT) and grip strength over 18 years among middle-aged and older African Caribbean men. We hypothesized that increases in IMAT precede the loss of muscle area and strength, and that increased IMAT is independently associated with strength decline. Men ( n = 339, 51.2 ± 5.5 years) were followed for 18.2 ± 0.9 years. Peripheral quantitative computed tomography at the calf determined IMAT (cm 2 ) and muscle area (cm 2 ) at baseline, follow-up visit 1 (FV1; 6.2 ± 0.4 years after baseline), and FV2 (12.0 ± 0.8 years after FV1). Grip strength (kg) was measured by handheld dynamometry at all visits. Generalized estimating equations determined associations between changes in IMAT and muscle area with time-varying grip strength. Grip strength decreased (mean ± SD, baseline: 51.33 ± 8.79, FV1: 47.02 ± 8.67, FV2: 40.12 ± 8.57), IMAT increased (median [quartile 1, quartile 3], baseline: 1.36 [0.73, 2.53], FV1: 1.74 [0.92, 3.14], FV2: 3.49 [2.06, 5.49]), and muscle area increased then decreased (baseline: 79.88 ± 12.33, FV1: 81.12 ± 13.88, FV2: 78.35 ± 12.72; all p < 0.05). A 1-cm 2 increase in IMAT from baseline to FV1 or FV2 was significantly associated with 0.18 kg (95% CI: −0.31, −0.06) decreased grip strength, independent of muscle area. The change in muscle area was not associated with grip strength declines ( β = 0.03, 95% CI: −0.03, 0.10). Despite initial muscle area increases, grip strength continuously decreased, and IMAT increased. Age-related increases in IMAT may contribute to the disconnect between declines in muscle strength and size. Graphical Abstract

Probabilistic forecasting for building energy systems using time-series foundation models - Young-Jin Park; François Germain; Jing Liu; Ye Wang; Toshiaki Koike-Akino; Gordon Wichern; Navid Azizan; Christopher Laughman; Ankush Chakrabarty (Energy and Buildings, 2025)

A generalised model of rainforest vulnerability to fire in eastern Australia - Christopher E. Gordon; Shiva Khanal; Rachael H. Nolan; Ross J. Peacock; Matthias M. Boer (Journal of Environmental Management, 2025)

Reactive inks: a feasibility study on self-evolving heterogeneous structures of Sr2+-based hydrogel driven by chemical potential - Nishat Paul; Joshua Lewis-Sandy; Bhaskar K C; Gordon Christopher; Minxiang Zeng (Chemical Engineering Journal, 2025)

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

Segment stability and transition between segments based on consumer perceived value towards energy efficiency: Implications for environmental management - Ross Gordon; Sally Dibb; Christopher Magee (Journal of Environmental Management, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Development of updated maintenance energy requirements of cattle using calorimeter data of growing cattle and suckler cows - Xianjiang Chen; Christopher K. Reynolds; Les A. Crompton; Francis Lively; Alan Gordon; Tianhai Yan (Livestock Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Scalable mangrove rehabilitation: Roots of success for Rhizophora stylosa establishment - Rory Mulloy; Christopher M. Aiken; Gordon Dwane; Megan Ellis; Emma L. Jackson (Ecological Engineering, 2025)

What to Measure in Aneurysmal Subarachnoid Haemorrhage Research—An International Delphi Survey - Christopher R. Andersen; Justin Presseau; Bev Shea; Maria Luisa Marti; Madeline McCoy; Gordon Fernie; Lauralyn McIntyre; Anthony Delaney; Michaël Chassé; Victoria Saigle; Shawn Marshall; Dean A. Fergusson; et al. (Translational Stroke Research, 2025)

Effects of nutrient fertilization and soil tillage on soil CO2 emissions in a long-term grassland experiment - Jonathan E. Holland; Dario Fornara; Alan Gordon; Christopher J. Boughton (Soil and Tillage Research, 2024)

The coupling of winds, ocean turbulence, and High Salinity Shelf Water in the Terra Nova Bay Polynya - Una Kim Miller; Christopher J. Zappa; Arnold L. Gordon; Seung-Tae Yoon; Craig Stevens; Liv Cornelissen; Sukyoung Yun; Won Sang Lee (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

Evaluating possible ‘next day’ impairment in insomnia patients administered an oral medicinal cannabis product by night: a pilot randomized controlled trial - Anastasia Suraev; Danielle McCartney; Nathaniel S. Marshall; Christopher Irwin; Ryan Vandrey; Ronald R. Grunstein; Angela L. D’Rozario; Christopher Gordon; Delwyn Bartlett; Camilla M. Hoyos; Iain S. McGregor (Psychopharmacology, 2024)
Cannabis and its major constituents, Δ 9 -tetrahydrocannabinol (THC) and cannabidiol (CBD), are being widely used to treat sleep disturbances. However, THC can cause acute cognitive and psychomotor impairment and there are concerns that driving and workplace safety might be compromised the day after evening use. Here, we examined possible ‘next day’ impairment following evening administration of a typical medicinal cannabis oil in adults with insomnia disorder, compared to matched placebo. This paper describes the secondary outcomes of a larger study investigating the effects of THC/CBD on insomnia disorder. Twenty adults [16 female; mean (SD) age, 46.1 (8.6) y] with physician-diagnosed insomnia who infrequently use cannabis completed two 24 h in-laboratory visits involving acute oral administration of combined 10 mg THC and 200 mg CBD (‘THC/CBD’) or placebo in a randomised, double-blind, crossover trial design. Outcome measures included ‘next day’ (≥9 h post-treatment) performance on cognitive and psychomotor function tasks, simulated driving performance, subjective drug effects, and mood. We found no differences in ‘next day’ performance on 27 out of 28 tests of cognitive and psychomotor function and simulated driving performance relative to placebo. THC/CBD produced a small decrease (-1.4%, p =.016, d =-0.6) in accuracy on the Stroop-Colour Task (easy/congruent) but not the Stroop-Word Task (hard/incongruent). THC/CBD also produced a small increase (+8.6, p =.042, d =0.3) in self-ratings of Sedated at 10 h post-treatment, but with no accompanying changes in subjective ratings of Alert or Sleepy ( p’s >0.05). In conclusion, we found a lack of notable ‘next day’ impairment to cognitive and psychomotor function and simulated driving performance following evening use of 10 mg oral THC, in combination with 200 mg CBD, in an insomnia population who infrequently use cannabis.

Whole-genome analyses converge to support the Hemirotifera hypothesis within Syndermata (Gnathifera) - Alexandros Vasilikopoulos; Holger Herlyn; Diego Fontaneto; Christopher Gordon Wilson; Reuben William Nowell; Jean-François Flot; Timothy Giles Barraclough; Karine Van Doninck (Hydrobiologia, 2024)

Enhanced potency of a chloro-substituted polyaromatic platinum(II) complex and its platinum(IV) prodrug against lung cancer - Joy Baz; Aleen Khoury; Maria George Elias; Najwa Mansour; Stephanie Mehanna; Omar Hammoud; Christopher P. Gordon; Robin I. Taleb; Janice R. Aldrich-Wright; Costantine F. Daher (Chemico-Biological Interactions, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Characterizing azobenzene disperse dyes and related compounds in house dust and their correlations with other organic contaminant classes - Kirsten E. Overdahl; Christopher D. Kassotis; Kate Hoffman; Gordon J. Getzinger; Allison Phillips; Stephanie Hammel; Heather M. Stapleton; P. Lee Ferguson (Environmental Pollution, 2023)

A census of quality-controlled Biogeochemical-Argo float measurements - Adam C. Stoer; Yuichiro Takeshita; Tanya Lea Maurer; Charlotte Begouen Demeaux; Henry C. Bittig; Emmanuel Boss; Hervé Claustre; Giorgio Dall’Olmo; Christopher Gordon; Blair John William Greenan; Kenneth S. Johnson; Emanuele Organelli; et al. (Frontiers in Marine Science, 2023)
Biogeochemical- (BGC-) Argo aims to deploy and maintain a global array of autonomous profiling floats to monitor ocean biogeochemistry. With over 250,000 profiles collected so far, the BGC-Argo network is rapidly expanding toward the target of a sustained fleet of 1,000 floats. These floats prioritize the measurement of six key properties: oxygen, nitrate, pH, chlorophyll-a, suspended particles, and downwelling light. To assess the current biogeochemical state of the ocean, its variability, and trends with confidence, it is crucial to quality control these measurements. Accordingly, BGC-Argo maintains a quality control system using manual inspection and parameter-specific algorithms for flagging and adjusting data. In this study, we provide a census of the quantity and quality of measurements from BGC-Argo based on their quality flagging system. The purpose of this census is to assess the current status of the array in terms of data quality, how data quality has changed over time, and to provide a better understanding of the quality-controlled data to current and future users. Alongside increasing profile numbers and spatial coverage, we report that for most parameters between 80 and 95% of the profiles collected so far contain high-quality BGC data, with an exception for pH. The quality of pH profiles has seen a large improvement in the last five years and is on track to match the data quality of other BGC parameters. We highlight how BGC-Argo is improving and discuss strategies to increase the quality and quantity of BGC profiles available to users. This census shows that tracking percentages of high-quality data through time is useful for monitoring float sensor technology and helpful for ensuring the long-term success of BGC-Argo.

Printability, texture, and sensory trade-offs for 3D printed potato with added proteins and lipids - Stefania Chirico Scheele; Martin Binks; Gordon Christopher; Farnaz Maleky; Paul F. Egan (Journal of Food Engineering, 2023)

Heat acclimation reduces the effects of whole-body hyperthermia on knee-extensor relaxation rate, but does not affect voluntary torque production - Ralph Joseph Frederick Hills Gordon; Jodie Natasha Moss; Federico Castelli; Thomas Reeve; Ceri Elen Diss; Christopher James Tyler; Neale Anthony Tillin (European Journal of Applied Physiology, 2023)
Purpose This study investigated the effects of acute hyperthermia and heat acclimation (HA) on maximal and rapid voluntary torque production, and their neuromuscular determinants. Methods Ten participants completed 10 days of isothermic HA (50 °C, 50% rh) and had their knee-extensor neuromuscular function assessed in normothermic and hyperthermic conditions, pre-, after 5 and after 10 days of HA. Electrically evoked twitch and octet (300 Hz) contractions were delivered at rest. Maximum voluntary torque (MVT), surface electromyography (EMG) normalised to maximal M-wave, and voluntary activation (VA) were assessed during brief maximal isometric voluntary contractions. Rate of torque development (RTD) and normalised EMG were measured during rapid voluntary contractions. Results Acute hyperthermia reduced neural drive (EMG at MVT and during rapid voluntary contractions; P < 0.05), increased evoked torques ( P < 0.05), and shortened contraction and relaxation rates ( P < 0.05). HA lowered resting rectal temperature and heart rate after 10 days ( P < 0.05), and increased sweating rate after 5 and 10 days ( P < 0.05), no differences were observed between 5 and 10 days. The hyperthermia-induced reduction in twitch half-relaxation was attenuated after 5 and 10 days of HA, but there were no other effects on neuromuscular function either in normothermic or hyperthermic conditions. Conclusion HA-induced favourable adaptations to the heat after 5 and 10 days of exposure, but there was no measurable benefit on voluntary neuromuscular function in normothermic or hyperthermic conditions. HA did reduce the hyperthermic-induced reduction in twitch half-relaxation time, which may benefit twitch force summation and thus help preserve voluntary torque in hot environmental conditions.

Integrating biological research, fisheries science and management of Pacific halibut (Hippoglossus stenolepis) across the North Pacific Ocean - Josep V. Planas; Christopher N. Rooper; Gordon H. Kruse (Fisheries Research, 2023)

Human health risk and food safety implications of microplastic consumption by fish from coastal waters of the eastern equatorial Atlantic Ocean - Edem Mahu; Wise Goodluck Datsomor; Regina Folorunsho; Jerome Fisayo; Richard Crane; Robert Marchant; Judith Montford; Mario Charles Boateng; Maurice Edusei Oti; Margret Ngozi Oguguah; Christopher Gordon (Food Control, 2023)

Evaluating the role of environmental familiarity and behaviour in the success of wildlife translocation: A grizzly bear case study using agent-based modelling - Alejandra Zubiria-Perez; Christopher Bone; Gordon Stenhouse (Ecological Complexity, 2023)

Production of an odor-reducing, low-dust, clumping cat litter from soybean hulls and soybean hull biochar - Steven F. Vaughn; Sean X. Liu; Mark A. Berhow; Jill K. Winkler-Moser; Steven C. Peterson; Gordon W. Selling; William T. Hay; Michael A. Jackson; Christopher D. Skory (Bioresource Technology Reports, 2023)

Contributions of healthier diets and agricultural productivity toward sustainability and climate goals in the United States - Grace C. Wu; Justin S. Baker; Christopher M. Wade; Gordon C. McCord; Joseph E. Fargione; Petr Havlik (Sustainability Science, 2023)
Meeting ambitious climate targets will require deploying the full suite of mitigation options, including those that indirectly reduce greenhouse-gas (GHG) emissions. Healthy diets have sustainability co-benefits by directly reducing livestock emissions as well as indirectly reducing land use emissions. Increased crop productivity could indirectly avoid emissions by reducing cropland area. However, there is disagreement on the sustainability of proposed healthy U.S. diets and a lack of clarity on how long-term sustainability benefits may change in response to shifts in the livestock sector. Here, we explore the GHG emissions impacts of seven scenarios that vary U.S. crop yields and healthier diets in the U.S. and overseas. We also examine how impacts vary across assumptions of future ruminant livestock productivity and ruminant stocking density in the U.S. We employ two complementary land use models—the US FABLE Calculator, an agricultural and forestry sector accounting model with high agricultural commodity representation, and GLOBIOM, a spatially explicit partial equilibrium optimization model for global land use systems. Results suggest that healthier U.S. diets that follow the Dietary Guidelines for Americans reduce agricultural and land use greenhouse gas emissions by 25–57% (approx 120–310 MtCO 2e /y) and pastureland area by 28–38%. The potential emissions and land sparing benefits of U.S. agricultural productivity growth are modest within the U.S. due to the increasing comparative advantage of U.S. crops. Our findings suggest that healthy U.S. diets can significantly contribute toward meeting U.S. long-term climate goals for the land use sectors.

Assessing levels of selected heavy metals with other pollutants in soil and water resources in Nandom District in the semi-arid northwestern Ghana - Ishmael Lente; William K. Heve; Maxwell Y. Owusu-Twum; Christopher Gordon; Pabi Opoku; Daniel Nukpezah; Richard Amfo-Otu (Environmental Monitoring and Assessment, 2022)

Environmental DNA Methods for Ecological Monitoring and Biodiversity Assessment in Estuaries - Raman P. Nagarajan; Mallory Bedwell; Ann E. Holmes; Thiago Sanches; Shawn Acuña; Melinda Baerwald; Matthew A. Barnes; Scott Blankenship; Richard E. Connon; Kristy Deiner; Daphne Gille; Caren S. Goldberg; et al. (Estuaries and Coasts, 2022)
Environmental DNA (eDNA) detection methods can complement traditional biomonitoring to yield new ecological insights in aquatic systems. However, the conceptual and methodological frameworks for aquatic eDNA detection and interpretation were developed primarily in freshwater environments and have not been well established for estuaries and marine environments that are by nature dynamic, turbid, and hydrologically complex. Environmental context and species life history are critical for successful application of eDNA methods, and the challenges associated with eDNA detection in estuaries were the subject of a symposium held at the University of California Davis on January 29, 2020 ( https://marinescience.ucdavis.edu/engagement/past-events/edna ). Here, we elaborate upon topics addressed in the symposium to evaluate eDNA methods in the context of monitoring and biodiversity studies in estuaries. We first provide a concise overview of eDNA science and methods, and then examine the San Francisco Estuary (SFE) as a case study to illustrate how eDNA detection can complement traditional monitoring programs and provide regional guidance on future potential eDNA applications. Additionally, we offer recommendations for enhancing communication between eDNA scientists and natural resource managers, which is essential for integrating eDNA methods into existing monitoring programs. Our intent is to create a resource that is accessible to those outside the field of eDNA, especially managers, without oversimplifying the challenges or advantages of these methods.

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Climate-smart agriculture: Greenhouse gas mitigation in climate-smart villages of Ghana - Samuel Weniga Anuga; Benedicta Yayra Fosu-Mensah; Daniel Nukpezah; Albert Ahenkan; Christopher Gordon; Richmond Silvanus Baye (Environmental Sustainability, 2022)
Climate-smart agriculture (CSA) is an approach that helps guide actions to transform agri-food systems towards green and climate-resilient practices and it remains prominent in food systems transformation in the light of increasing climate change impacts. Unfortunately, the quantification of the greenhouse gas (GHG) mitigation potential of CSA approaches is currently limited. Using the Cool Farm Tool (CFT), this paper quantifies the GHG mitigation of CSA based on farm-level experimental data. Individual interviews and focus group discussions were also conducted to identify farmers’ choices and willingness to adopt CSA practices. The study compared the GHG emission mitigation of CSA practices for two scenarios (baseline and mitigation). The study found that organic fertilizer input, residue incorporation, no-inorganic fertilizer and no-pesticide input reduced GHG emission intensity of sorghum (to 93.2 ± 25 kg CO 2 e GHG kg − 1 sorghum), rice (79.2 ± 22 kg CO 2 e GHG kg − 1 rice) and groundnut (69.7 ± 20 kg CO 2 e GHG kg − 1 groundnut) compared to the baseline. Lower GHG emission intensity was achieved with higher crop yield under CSA interventions. The study recommends that CSA promoters such as the Consultative Group for International Agriculture Research (CGIAR), Food and Agriculture Organization (FAO) and the World Bank focus on crop-specific CSA practices for higher GHG mitigation. CSA promoters such as the CGIAR, FAO and the World Bank should embrace participatory processes such as farmer schools to increase CSA uptake.

Heavy Metal Pollution in the Surface Sediments from Cage Aquaculture Farms in the Volta Basin of Ghana: Source Identification and Ecological Risk Assessment - Emmanuel Kaboja Magna; Samuel Senyo Koranteng; Augustine Donkor; Christopher Gordon (Water, Air, & Soil Pollution, 2022)

Levels of Persistent Organochlorine Compounds in Nile Tilapia (Oreochromis niloticus) from Three Cage Aquaculture Farms on the Volta Basin of Ghana: Implications for Human Health - Emmanuel Kaboja Magna; Samuel Senyo Koranteng; Augustine Donkor; Christopher Gordon (Environmental Processes, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Two heads are better than one: current landscape of integrating QSP and machine learning - Tongli Zhang; Ioannis P. Androulakis; Peter Bonate; Limei Cheng; Tomáš Helikar; Jaimit Parikh; Christopher Rackauckas; Kalyanasundaram Subramanian; Carolyn R. Cho; Ioannis P. Androulakis; Peter Bonate; Ivan Borisov; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2022)
Quantitative systems pharmacology (QSP) modeling is applied to address essential questions in drug development, such as the mechanism of action of a therapeutic agent and the progression of disease. Meanwhile, machine learning (ML) approaches also contribute to answering these questions via the analysis of multi-layer ‘omics’ data such as gene expression, proteomics, metabolomics, and high-throughput imaging. Furthermore, ML approaches can also be applied to aspects of QSP modeling. Both approaches are powerful tools and there is considerable interest in integrating QSP modeling and ML. So far, a few successful implementations have been carried out from which we have learned about how each approach can overcome unique limitations of the other. The QSP + ML working group of the International Society of Pharmacometrics QSP Special Interest Group was convened in September, 2019 to identify and begin realizing new opportunities in QSP and ML integration. The working group, which comprises 21 members representing 18 academic and industry organizations, has identified four categories of current research activity which will be described herein together with case studies of applications to drug development decision making. The working group also concluded that the integration of QSP and ML is still in its early stages of moving from evaluating available technical tools to building case studies. This paper reports on this fast-moving field and serves as a foundation for future codification of best practices.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Organochlorine Pesticides and Polychlorinated Biphenyls in Sediment Impacted by Cage Aquaculture in the Volta Basin of Ghana - Emmanuel Kaboja Magna; Samuel Senyo Koranteng; Augustine Donkor; Christopher Gordon (Archives of Environmental Contamination and Toxicology, 2022)

Differential household vulnerability to climatic and non-climatic stressors in semi-arid areas of Mali, West Africa - Alcade C. Segnon; Edmond Totin; Robert B. Zougmoré; Jourdain C. Lokossou; Mary Thompson-Hall; Benjamin O. Ofori; Enoch G. Achigan-Dako; Christopher Gordon (Climate and Development, 2021)

The long and narrow path for novel cell‐based seafood to reduce fishing pressure for marine ecosystem recovery - Benjamin S. Halpern; Jason Maier; Heather J. Lahr; Gordon Blasco; Christopher Costello; Richard S. Cottrell; Olivier Deschenes; Danielle M. Ferraro; Halley E. Froehlich; Gavin G. McDonald; Katherine D. Millage; Michael J. Weir (Fish and Fisheries, 2021)
Cell‐based seafood is an emerging novel food, with many start‐up companies aspiring for ocean conservation benefits through expanded market share that displaces wild‐caught seafood. However, the ability for cell‐based seafood to achieve this conservation outcome is often oversimplified and will rely on an extensive, and we find somewhat tenuous, chain of events. Here, we outline the technological, behavioural, market and ecological changes that must occur along this pathway, and conclude that fisheries recoveries and collateral ocean benefits are unlikely to result from cell‐based seafood technology. In particular, we detail nine necessary steps and argue that failure at any one step could hinder or even eliminate cell‐based seafood's conservation effects. We additionally draw comparisons to aquaculture and share broader lessons for other demand‐driven product interventions.

Elephant rewilding indirectly affects the abundance of an arboreal but not generalist savanna lizard - Christopher E. Gordon; Rion E. Lerm; Paul Allin; Michelle Greve; Jens-Christian Svenning (Biodiversity and Conservation, 2021)

Practical challenges to the clinical implementation of saliva for SARS-CoV-2 detection - Nancy Matic; Aleksandra Stefanovic; Victor Leung; Tanya Lawson; Gordon Ritchie; Lynne Li; Sylvie Champagne; Marc G. Romney; Christopher F. Lowe (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Iron and zinc homeostases in female rats with physically active and sedentary lifestyles - Andrew J. Ghio; Joleen M. Soukup; Caroline Ghio; Christopher J. Gordon; Judy E. Richards; Mette C. Schladweiler; Samantha J. Snow; Urmila P. Kodavanti (BioMetals, 2021)

Preparing interdisciplinary leadership for a sustainable future - Christopher G. Boone; Steward T. A. Pickett; Gabriele Bammer; Kamal Bawa; Jennifer A. Dunne; Iain J. Gordon; David Hart; Jessica Hellmann; Alison Miller; Mark New; Jean P. Ometto; Ken Taylor; et al. (Sustainability Science, 2020)

OpenMendel: a cooperative programming project for statistical genetics - Hua Zhou; Janet S. Sinsheimer; Douglas M. Bates; Benjamin B. Chu; Christopher A. German; Sarah S. Ji; Kevin L. Keys; Juhyun Kim; Seyoon Ko; Gordon D. Mosher; Jeanette C. Papp; Eric M. Sobel; et al. (Human Genetics, 2020)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Consecutive days of exercise decrease insulin response more than a single exercise session in healthy, inactive men - Todd Castleberry; Christopher Irvine; Sarah E. Deemer; Matthew F. Brisebois; Ryan Gordon; Michael D. Oldham; Anthony A. Duplanty; Vic Ben-Ezra (European Journal of Applied Physiology, 2019)

Precision and accuracy of Dahl‐Lea back‐calculated smolt lengths from adult scales of Atlantic salmon Salmo salar - Nora N. Hanson; Gordon W. Smith; Stuart J. Middlemas; Christopher D. Todd (Journal of Fish Biology, 2019)
Using tagged and recaptured Atlantic salmon Salmo salar (n = 106) the present analysis shows that the most commonly applied linear back‐calculation method for estimating past length, the Dahl‐Lea method, resulted in overestimation of the length of large smolts and underestimation of small smolts. A correction equation ( y = 0.53 x + 6.23) for estimating true smolt length ( y ) from lengths back‐calculated from adult scale measures ( x ) to account for these systematic discrepancies is proposed.

Fungi at the Scene of the Crime: Innocent Bystanders or Accomplices in Oral Infections? - Christopher Delaney; Ryan Kean; Bryn Short; Maria Tumelty; William McLean; Christopher J. Nile; Gordon Ramage (Current Clinical Microbiology Reports, 2018)

Aboveground carbon sequestration in dry temperate forests varies with climate not fire regime - Christopher E. Gordon; Eli R. Bendall; Mitchell G. Stares; Luke Collins; Ross A. Bradstock (Global Change Biology, 2018)
The storage of carbon in plant tissues and debris has been proposed as a method to offset anthropogenic increases in atmospheric [ CO 2 ]. Temperate forests represent significant above‐ground carbon ( AGC ) “sinks” because their relatively fast growth and slow decay rates optimise carbon assimilation. Fire is a common disturbance event in temperate forests globally that should strongly influence AGC because: discrete fires consume above‐ground biomass releasing carbon to the atmosphere, and the long‐term application of different fire‐regimes select for specific plant communities that sequester carbon at different rates. We investigated the latter process by quantifying AGC storage at 104 sites in the Sydney Basin Bioregion, Australia, relative to differences in components of the fire regime: frequency, severity and interfire interval. To predict the potential impacts of future climate change on fire/ AGC interactions, we stratified our field sites across gradients of mean annual temperature and precipitation and quantified within‐ and between‐factor interactions between the fire and climate variables. In agreement with previous studies, large trees were the primary AGC sink, accounting for ~70% of carbon at sites. Generalised additive models showed that mean annual temperature was the strongest predictor of AGC storage, with a 54% near‐linear decrease predicted across the 6.1°C temperature range experienced at sites. Mean annual precipitation, fire frequency, fire severity and interfire interval were consistently poor predictors of total above‐ground storage, although there were some significant relationships with component stocks. Our results show resilience of AGC to frequent and severe wildfire and suggest temperature mediated decreases in forest carbon storage under future climate change predictions.

Invasive cane toads might initiate cascades of direct and indirect effects in a terrestrial ecosystem - Benjamin Feit; Christopher E. Gordon; Jonathan K. Webb; Tim S. Jessop; Shawn W. Laffan; Tim Dempster; Mike Letnic (Biological Invasions, 2018)

Abnormal social behavior in mice with tyrosinemia type I is associated with an increase of myelin in the cerebral cortex - Marissa E. Moore; Ashton E. Koenig; Megan A. Hillgartner; Christopher C. Otap; Elizabeth Barnby; Gordon G. MacGregor (Metabolic Brain Disease, 2017)

Signatures of polygenic adaptation associated with climate across the range of a threatened fish species with high genetic connectivity - Katherine A. Harrisson; Stephen J. Amish; Alexandra Pavlova; Shawn R. Narum; Marina Telonis‐Scott; Meaghan L. Rourke; Jarod Lyon; Zeb Tonkin; Dean M. Gilligan; Brett A. Ingram; Mark Lintermans; Han Ming Gan; et al. (Molecular Ecology, 2017)
Adaptive differences across species’ ranges can have important implications for population persistence and conservation management decisions. Despite advances in genomic technologies, detecting adaptive variation in natural populations remains challenging. Key challenges in gene–environment association studies involve distinguishing the effects of drift from those of selection and identifying subtle signatures of polygenic adaptation. We used paired‐end restriction site‐associated DNA sequencing data (6,605 biallelic single nucleotide polymorphisms; SNP s) to examine population structure and test for signatures of adaptation across the geographic range of an iconic Australian endemic freshwater fish species, the Murray cod Maccullochella peelii . Two univariate gene–association methods identified 61 genomic regions associated with climate variation. We also tested for subtle signatures of polygenic adaptation using a multivariate method (redundancy analysis; RDA ). The RDA analysis suggested that climate (temperature‐ and precipitation‐related variables) and geography had similar magnitudes of effect in shaping the distribution of SNP genotypes across the sampled range of Murray cod. Although there was poor agreement among the candidate SNP s identified by the univariate methods, the top 5% of SNP s contributing to significant RDA axes included 67% of the SNP s identified by univariate methods. We discuss the potential implications of our findings for the management of Murray cod and other species generally, particularly in relation to informing conservation actions such as translocations to improve evolutionary resilience of natural populations. Our results highlight the value of using a combination of different approaches, including polygenic methods, when testing for signatures of adaptation in landscape genomic studies.

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Temporal and spatial trends in the abundances of an apex predator, introduced mesopredator and ground-nesting bird are consistent with the mesopredator release hypothesis - Christopher E. Gordon; Ben D. Moore; Mike Letnic (Biodiversity and Conservation, 2017)

Influenza transmission during extreme indoor conditions in a low-resource tropical setting - James Tamerius; Sergio Ojeda; Christopher K. Uejio; Jeffrey Shaman; Brenda Lopez; Nery Sanchez; Aubree Gordon (International Journal of Biometeorology, 2017)

Ensemble ecosystem modeling for predicting ecosystem response to predator reintroduction - Christopher M. Baker; Ascelin Gordon; Michael Bode (Conservation Biology, 2017)
Introducing a new or extirpated species to an ecosystem is risky, and managers need quantitative methods that can predict the consequences for the recipient ecosystem. Proponents of keystone predator reintroductions commonly argue that the presence of the predator will restore ecosystem function, but this has not always been the case, and mathematical modeling has an important role to play in predicting how reintroductions will likely play out. We devised an ensemble modeling method that integrates species interaction networks and dynamic community simulations and used it to describe the range of plausible consequences of 2 keystone‐predator reintroductions: wolves (Canis lupus) to Yellowstone National Park and dingoes (Canis dingo) to a national park in Australia. Although previous methods for predicting ecosystem responses to such interventions focused on predicting changes around a given equilibrium, we used Lotka–Volterra equations to predict changing abundances through time. We applied our method to interaction networks for wolves in Yellowstone National Park and for dingoes in Australia. Our model replicated the observed dynamics in Yellowstone National Park and produced a larger range of potential outcomes for the dingo network. However, we also found that changes in small vertebrates or invertebrates gave a good indication about the potential future state of the system. Our method allowed us to predict when the systems were far from equilibrium. Our results showed that the method can also be used to predict which species may increase or decrease following a reintroduction and can identify species that are important to monitor (i.e., species whose changes in abundance give extra insight into broad changes in the system). Ensemble ecosystem modeling can also be applied to assess the ecosystem‐wide implications of other types of interventions including assisted migration, biocontrol, and invasive species eradication.

Low-quality sediments deter grazing by the parrotfish Scarus rivulatus on inner-shelf reefs - Sophie E. Gordon; Christopher H. R. Goatley; David R. Bellwood (Coral Reefs, 2016)

Fatty Acid Binding Proteins Expressed at the Human Blood–Brain Barrier Bind Drugs in an Isoform-Specific Manner - Gordon S. Lee; Katharina Kappler; Christopher J. H. Porter; Martin J. Scanlon; Joseph A. Nicolazzo (Pharmaceutical Research, 2015)

Erratum to: Clinical associations between IL-17 family cytokines and periodontitis and potential differential roles for IL-17A and IL-17E in periodontal immunity - Raja Azman Awang; David F. Lappin; Alexandrea MacPherson; Marcello Riggio; Douglas Robertson; Penny Hodge; Gordon Ramage; Shauna Culshaw; Philip M. Preshaw; John Taylor; Christopher Nile (Inflammation Research, 2015)

Clinical associations between IL-17 family cytokines and periodontitis and potential differential roles for IL-17A and IL-17E in periodontal immunity - Raja Azman; David F. Lappin; Alexandrea MacPherson; Marcello Riggio; Douglas Robertson; Penny Hodge; Gordon Ramage; Shauna Culshaw; Philip M. Preshaw; John Taylor; Christopher Nile (Inflammation Research, 2014)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Widespread variability in overnight patterns of ecosystem respiration linked to gradients in dissolved organic matter, residence time, and productivity in a global set of lakes - Steven Sadro; Gordon W. Holtgrieve; Christopher T. Solomon; Gregory R. Koch (Limnology and Oceanography, 2014)
We characterized patterns of nighttime ecosystem respiration (ER) in 23 globally‐distributed lakes using free‐water changes in dissolved oxygen (DO). We considered three alternative models of ER to describe overnight changes in DO: constant ER, linearly declining ER, or logistically declining ER. Variation in ER was widespread. Each model of respiration was found to best fit observed overnight DO dynamics with some degree of frequency in every lake. Constant ER occurred with an average frequency of 62% across lakes and was most commonly the best description of DO dynamics. It never occurred with a frequency

Integrating Biological and Social Values When Prioritizing Places for Biodiversity Conservation - AMY L. WHITEHEAD; HEINI KUJALA; CHRISTOPHER D. IVES; ASCELIN GORDON; PIA E. LENTINI; BRENDAN A. WINTLE; EMILY NICHOLSON; CHRISTOPHER M. RAYMOND (Conservation Biology, 2014)
The consideration of information on social values in conjunction with biological data is critical for achieving both socially acceptable and scientifically defensible conservation planning outcomes. However, the influence of social values on spatial conservation priorities has received limited attention and is poorly understood. We present an approach that incorporates quantitative data on social values for conservation and social preferences for development into spatial conservation planning. We undertook a public participation GIS survey to spatially represent social values and development preferences and used species distribution models for 7 threatened fauna species to represent biological values. These spatially explicit data were simultaneously included in the conservation planning software Zonation to examine how conservation priorities changed with the inclusion of social data. Integrating spatially explicit information about social values and development preferences with biological data produced prioritizations that differed spatially from the solution based on only biological data. However, the integrated solutions protected a similar proportion of the species’ distributions, indicating that Zonation effectively combined the biological and social data to produce socially feasible conservation solutions of approximately equivalent biological value. We were able to identify areas of the landscape where synergies and conflicts between different value sets are likely to occur. Identification of these synergies and conflicts will allow decision makers to target communication strategies to specific areas and ensure effective community engagement and positive conservation outcomes. Integración de Valores Biológicos y Sociales al Priorizar Sitios para la Conservación de la Biodiversidad

The alpha 7 nicotinic receptor agonist PHA-543613 hydrochloride inhibits Porphyromonas gingivalis-induced expression of interleukin-8 by oral keratinocytes - Alexandrea Macpherson; Noha Zoheir; Raja Azman Awang; Shauna Culshaw; Gordon Ramage; David F. Lappin; Christopher J. Nile (Inflammation Research, 2014)

Animating the Carbon Cycle - Oswald J. Schmitz; Peter A. Raymond; James A. Estes; Werner A. Kurz; Gordon W. Holtgrieve; Mark E. Ritchie; Daniel E. Schindler; Amanda C. Spivak; Rod W. Wilson; Mark A. Bradford; Villy Christensen; Linda Deegan; et al. (Ecosystems, 2014)

A Hydrological Budget (2002–2008) for a Large Subtropical Wetland Ecosystem Indicates Marine Groundwater Discharge Accompanies Diminished Freshwater Flow - Amartya K. Saha; Christopher S. Moses; René M. Price; Victor Engel; Thomas J. Smith; Gordon Anderson (Estuaries and Coasts, 2012)

Using digital time-lapse cameras to monitor species-specific understorey and overstorey phenology in support of wildlife habitat assessment - Christopher W. Bater; Nicholas C. Coops; Michael A. Wulder; Thomas Hilker; Scott E. Nielsen; Greg McDermid; Gordon B. Stenhouse (Environmental Monitoring and Assessment, 2011)

The bioinvasion of Guam: inferring geographic origin, pace, pattern and process of an invasive lizard (Carlia) in the Pacific using multi-locus genomic data - Christopher C. Austin; Eric N. Rittmeyer; Lauren A. Oliver; John O. Andermann; George R. Zug; Gordon H. Rodda; Nathan D. Jackson (Biological Invasions, 2011)

Fingertip photoplethysmographic waveform variability and systemic vascular resistance in intensive care unit patients - Paul M. Middleton; Gregory S. H. Chan; Elizabeth Steel; Philip Malouf; Christopher Critoph; Gordon Flynn; Emma O’Lone; Branko G. Celler; Nigel H. Lovell (Medical & Biological Engineering & Computing, 2011)

Climate change links fate of glaciers and an endemic alpine invertebrate - Clint C. Muhlfeld; J. Joseph Giersch; F. Richard Hauer; Gregory T. Pederson; Gordon Luikart; Douglas P. Peterson; Christopher C. Downs; Daniel B. Fagre (Climatic Change, 2011)

Federated Access to Heterogeneous Information Resources in the Neuroscience Information Framework (NIF) - Amarnath Gupta; William Bug; Luis Marenco; Xufei Qian; Christopher Condit; Arun Rangarajan; Hans Michael Müller; Perry L. Miller; Brian Sanders; Jeffrey S. Grethe; Vadim Astakhov; Gordon Shepherd; et al. (Neuroinformatics, 2008)

Male parentage in dependent‐lineage populations of the harvester ant Pogonomyrmex barbatus - SEVAN S. SUNI; CHRISTOPHER GIGNOUX; DEBORAH M. GORDON (Molecular Ecology, 2007)
We investigated the extent to which workers reproduce in a dependent‐lineage population of the monogynous harvester ant Pogonomyrmex barbatus. Dependent‐lineage populations contain two interbreeding, yet genetically distinct mitochondrial lineages, each associated with specific alleles at nuclear loci. Workers develop from matings between lineages, and queens develop from matings within lineages, so queens must mate with males of both lineages to produce daughter queens and workers. Males develop from unfertilized eggs and are haploid. Worker production of males could lead to male‐mediated gene flow between the lineages if worker‐produced males were reproductively capable. This could result in the loss of the dependent‐lineage system, because its persistence depends on the maintenance of allelic differences between the lineages. To investigate the extent of worker reproduction in P. barbatus , we genotyped 19–20 males and workers from seven colonies, at seven microsatellite loci, and 1239 additional males at two microsatellite loci. Our methods were powerful enough to detect worker reproduction if workers produced more than 0.39% of males in the population. We detected no worker‐produced males; all males appeared to be produced by queens. Thus, worker reproduction is sufficiently infrequent to have little impact on the dependent‐lineage system. These results are consistent with predictions based on inclusive fitness theory because the effective queen mating frequency calculated from worker genotypes was 4.26, which is sufficiently high for workers to police those that attempt to reproduce.

A TNF region haplotype offers protection from typhoid fever in Vietnamese patients - Sarah J. Dunstan; Nguyen Thi Hue; Kirk Rockett; Julian Forton; Andrew P. Morris; Mahamadou Diakite; Mai Ngoc Lanh; Le Thi Phuong; Deborah House; Christopher M. Parry; Ha Vinh; Nguyen T. Hieu; et al. (Human Genetics, 2007)

Multiple-methods investigation of recharge at a humid-region fractured rock site, Pennsylvania, USA - Christopher S. Heppner; John R. Nimmo; Gordon J. Folmar; William J. Gburek; Dennis W. Risser (Hydrogeology Journal, 2007)

Why is it Challenging to Predict Intestinal Drug Absorption and Oral Bioavailability in Human Using Rat Model - Xianhua Cao; Seth T. Gibbs; Lanyan Fang; Heather A. Miller; Christopher P. Landowski; Ho-Chul Shin; Hans Lennernas; Yanqiang Zhong; Gordon L. Amidon; Lawrence X. Yu; Duxin Sun (Pharmaceutical Research, 2006)

Effects of chronic exercise conditioning on thermal responses to lipopolysaccharide and turpentine abscess in female rats - Pamela Johnson Rowsey; Bonnie L. Metzger; John Carlson; Christopher J. Gordon (Archives of Toxicology, 2006)

Floxuridine Amino Acid Ester Prodrugs: Enhancing Caco-2 Permeability and Resistance to Glycosidic Bond Metabolism - Christopher P. Landowski; Xueqin Song; Philip L. Lorenzi; John M. Hilfinger; Gordon L. Amidon (Pharmaceutical Research, 2005)

Transporter and ion channel gene expression after caco-2 cell differentiation using 2 different microarray technologies - Christopher P. Landowski; Pascale Anderle; Duxin Sun; Wolfgang Sadee; Gordon L. Amidon (The AAPS Journal, 2004)

A Fluorescent hPept1 Transporter Substrate for Uptake Screening - Christopher P. Landowski; Hyo-kyung Han; Kyung-Dall Lee; Gordon L. Amidon (Pharmaceutical Research, 2003)

Amino Acid Ester Prodrugs of Floxuridine: Synthesis and Effects of Structure, Stereochemistry, and Site of Esterification on the Rate of Hydrolysis - Balvinder S. Vig; Philip J. Lorenzi; Sachin Mittal; Christopher P. Landowski; Ho-Chul Shin; Henry I. Mosberg; John M. Hilfinger; Gordon L. Amidon (Pharmaceutical Research, 2003)

Organization of Carboxysome Genes in the Thiobacilli - Gordon C. Cannon; Stefanie H. Baker; Ferda Soyer; Diana R. Johnson; Christopher E. Bradburne; Jennifer L. Mehlman; Paige S. Davies; Qin Li Jiang; Sabine Heinhorst; Jessup M. Shively (Current Microbiology, 2003)

Comparison of Human Duodenum and Caco-2 Gene Expression Profiles for 12,000 Gene Sequences Tags and Correlation with Permeability of 26 Drugs - Duxin Sun; Hans Lennernas; Lynda S. Welage; Jeffery L. Barnett; Christopher P. Landowski; David Foster; David Fleisher; Kyung-Dall Lee; Gordon L. Amidon (Pharmaceutical Research, 2002)

Reliable short-term memory in the trion model: toward a cortical language and grammar - Milind Sardesai; Christopher Figge; Mark Bodner; Meridith Crosby; Jill Hansen; Jorge A. Quillfeldt; Susan Landau; Annette Ostling; Sydni Vuong; Gordon L. Shaw (Biological Cybernetics, 2001)

Intracellular localization and trafficking of steroid receptors - Christopher T. Baumann; Carol S. Lim; Gordon L. Hager (Cell Biochemistry and Biophysics, 1999)

Evidence for Overlapping Substrate Specificity Between Large Neutral Amino Acid (LNAA) and Dipeptide (hPEPTl) Transporters for PD 158473, an NMDA Antagonist - Narayanan Surendran; Kuang-Ming Y. Covitz; Hyo-kyung Han; Wolfgang Sadee; Doo-Man Oh; Gordon L. Amidon; Rufus M. Williamson; Christopher F. Bigge; Barbra H. Stewart (Pharmaceutical Research, 1999)

Effects of Solar UV‐B Radiation on Embryonic Development in Hyla cadaverina, Hyla regilla, and Taricha torosa - Christopher R. Anzalone; Lee B. Kats; Malcolm S. Gordon (Conservation Biology, 1998)
Exposure to solar ultraviolet‐B (UV‐B) radiation leads to increased embryonic mortality in some amphibians. It has been hypothesized that sensitivity to UV‐B may contribute to the population declines of some species. To better understand the effects of ambient UV‐B on embryo development and survival, embryos from three lower latitude (34°N), lower altitude (290 m) amphibian species were studied at natural breeding sites in the Santa Monica Mountains near Los Angeles, California. We compared embryonic development and hatching success in Hyla regilla , Hyla cadaverina , and Taricha torosa embryos exposed to ambient solar UV‐B radiation with those shielded from solar UV‐B. A large percentage of H. regilla embryos survived when exposed to and protected from UV‐B. Neither hatching success nor rates of development were affected by solar UV‐B. Conversely, H. cadaverina and T. torosa embryos displayed high rates of embryonic mortality when exposed to solar UV‐B. Elimination of solar UV‐B significantly increased hatching success in both of these species, but had no effect on rates of embryonic development. These data suggest that under natural conditions, solar UV‐B radiation influences embryo survival in both Hyla cadaverina and Taricha torosa . Additional studies are required to determine whether susceptibility to UV‐B affects these species at the population level. Efecto de la Radiación Solar UV‐B en el Desarrollo Embrionario en Hyla cadaverina , Hyla regilla y Taricha torosa La exposición a radiación solar ultravioleta‐B (UV‐B) resulta en el incremento de la mortalidad embrionaria en algunos anfibios. Existe la hipótesis de que la sensibilidad a UV‐B puede contribuir a la declinación poblacional de algunas especies. Para entender los efectos de UV‐B ambiental sobre el desarrollo y sobrevivencia embrionario estudiamos, en sitios reproductivos naturales cerca de Los Angeles California, embriones de especies de anfibios de baja latitud (34 ° N) y baja altitud. Comparamos el desarrollo embrionario y éxito de eclosión en embriones de Hyla cadaverina , Hyla regilla y Taricha torosa expuestos a radiación UV‐B ambiente con los de embriones protegidos de la radiación. Un alto porcentaje de embriones de H. regilla sobrevivió cuando expuestos a y protegidos de la radiación. La radiación UV‐B no afectó al éxito de eclosión ni a las tasas de desarrollo. Por el contrario, embriones de H. cadaverina y T. torosa presentaron altas tasas de mortalidad embrionaria cuando expuestos a la radiación UV‐B. La eliminación de UV‐B incrementó el éxito de eclosión significativamente en ambas especies, pero no tuvo efecto sobre las tasas de desarrollo embrionario. Estos datos sugieren que, en condiciones naturales, la radiación UV‐B influye sobre la sobrevivencia de Hyla cadaverina y Taricha torosa . Se requieren estudios adicionales para determinar si la susceptibilidad a UV‐B afecta a estas especies a nivel poblacional.

Effects of Solar UV-B Radiation on Embryonic Development in Hyla cadaverina, Hyla regilla, and Taricha torosa - Christopher R. Anzalone; Lee B. Kats; Malcolm S. Gordon (Conservation Biology, 1998)

Dissociation of force production from MHC and actin contents in muscles injured by eccentric contractions - Christopher P. Ingalls; Gordon L. Warren; R. B. Armstrong (Journal of Muscle Research and Cell Motility, 1998)

Thermoregulatory responses of the rabbit to subcutaneous injection of sulfolane - Forrest S. Mohler; Christopher J. Gordon (Archives of Toxicology, 1988)

Effect of ambient temperature on the hypometabolic and hypothermic effects of sulfolane in rats - Christopher J. Gordon; Merritt D. Long; Robert S. Dyer (Archives of Toxicology, 1984)